Structural and sensory analysis of compositionally optimized apple jellies enriched with dietary fibre compared to commercial apple jams - Figueroa, Lilian Elisa (2019)
The objective of this work was to optimize the formulation of apple jellies enriched with 3 g/100 g of dietary fibre and to compare them with commercial apple jams in terms of structural and organoleptic properties. With that aim, a fibre mix with one part of psyllium and three parts of other fibre variety (apple, bamboo or wheat) was added to apple jelly, and the rheological, mechanical and sensory properties, as well as colour and syneresis (water loss) of the samples at different storage times were studied, and compared to two commercial apple jams. Those properties did not suffer significant changes during 30 days of cold storage, meaning that the product was stable. The reduction of psyllium proportion in the fibre mix (from 1:1 to 1:3) reduced the gumminess of the fibre enriched jellies, keeping the syneresis at 0 g/100 g. The jelly enriched with apple and psyllium fibre was the most similar to commercial apple jams in terms of rheological and mechanical properties. Consumers acceptability of fibre enriched jellies was higher than 72%, being the jelly enriched with bamboo and psyllium fibre the closest to a commercial apple jam, which was consumer’s favourite.